Genomic and Functional Characterization of Enterococcus mundtii QAUEM2808, Isolated From Artisanal Fermented Milk Product Dahi - Nawaz, Farah; Khan, Muhammad Nadeem; Javed, Aqib; Ahmed, Ibrar; Ali, Naeem; Ali, Muhammad Ishtiaq; Bakhtiar, Syeda Mariam; Imran, Muhammad (Frontiers in Microbiology, 2019)
Microbial strains with a unique combination of technological and bioactive properties are preferred for industrial applications. The present study was conducted to evaluate the potential use of Enterococcus mundtii QAUEM2808 (NCBI Accession Number: LSMC00000000) in milk fermentation. This strain was isolated from Dahi, an indigenous fermented milk product of South-East Asia. The in vitro study confirmed the acidification ability as well as the proteolytic, cellulolytic, and amylolytic enzyme activities of this strain. It also produced a substantial amount of the folate in laboratory media and no physiological dysfunctions in laboratory animals was observed in feeding trials. All these properties were confirmed by in silico genome analysis. The Enterococcus mundtii QAUEM2808 genome consisted of a single, circular chromosome comprising 2,957,300-bp, 2,587 genes with GC content of 38.5%. Moreover, 16t RNAs, 1, 3 (16S, 23S) rRNAs, 4 ncRNAs, and 91 pseudo genes were also predicted. The majority of genome encode genes for protein, amino acids, carbohydrate, cell wall DNA and RNA metabolisms including all genes required for conversion of lactose to lactic acid. It also exhibited antimicrobial activity against E. coli ATCC 10536, S. aureus ATCC 6538, P. aeruginosa ATCC 9027, and L. monocytogenes ATCC 13932 and was found to be sensitive to commonly used antibiotics. The in silico analysis revealed the presence of genes for mundaticin and enterocin production, and CRISPER regions, however, the genes for antibiotic resistance were absent. No genes related to the pathogenicity island and prophages were detected by genome mining. Therefore, it could be inferened that Enterococcus mundtii QAUEM2808 has the potential to be used in milk fermentation as adjunct culture.